Mie kering dengan substitusi tepung telur ayam ras (Gallus gallus domesticus) - Sherina Melianti; Triana Ulfah; Rachmat Adiputra; Ati Atul Quddus; Atia Fizriani; Hari Hariadi (Composite : Jurnal Ilmu Pertanian, 2021)
This research was purposed to determine the effect of the addition of egg powder on physicochemical properties and to determine the best formulation treatment according to organoleptic properties. This study used a one-factor Randomized group design (RAK) with 4 treatments (A0: 100% flour, A1: 90% flour + 10% egg flour, A2 : 80% flour + 20% egg flour, A3 : 70% flour + 30% egg flour) and 3 repetitions. The results showed that the combination of adding egg flour had no significant effect on chemical characteristics (ash content), on physical characteristics the combination of adding egg flour had a significant effect on physical properties. The best formulation based on organoleptic properties was the addition of 10% egg flour on texture parameters 5.00 (liked), aroma 4.80 (liked), taste 5.13 (liked), color 5.45 (liked).